Transcriptomic Changes and Pathological Mechanisms in Familial and Sporadic Idiopathic Restless Legs Syndrome: Implications for Inflammation and Cell Adhesion Molecules - He XR; Song JM; Zhao JP; Zhang J; Feng JT; Chen SQ; Zhou ZY; Wang HM; Zhang Y; Feng Y; Wu YC; Zhu XY (Nature and Science of Sleep, 2025)
Xin-Rong He,1,* Jia-Min Song,1,* Jia-Peng Zhao,2 Jing Zhang,1 Jing-Tao Feng,1 Shu-Qin Chen,3 Zhi-Yuan Zhou,1 Hong-Ming Wang,4 Yue Zhang,5 Ya Feng,1 Yun-Cheng Wu,1 Xiao-Ying Zhu1 1Department of Neurology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China; 2Department of Orthopedics, Yongxiu County Traditional Chinese Medicine Hospital in Jiujiang City, Jiangxi, 330304, People’s Republic of China; 3Community Health Service Center, Ouyang Road District, Hongkou District, Shanghai, 200080, People’s Republic of China; 4Department of Clinical Laboratory Medicine, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China; 5Department of Bioinformatics and Biostatistics, School of Life Sciences and Biotechnology, Shanghai Jiao Tong University, Shanghai, 200240, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun-Cheng Wu, Department of Neurology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China, Tel +86-21-63240090, Email drwu2006@163.com Xiao-Ying Zhu, Department of Neurology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China, Email docxiaoying@163.comPurpose: Individuals affected by restless legs syndrome (RLS) tend to have familial predispositions without fully explained by genetic variants, and transcriptomic analysis may help elucidate the pathogenic mechanisms of RLS. The study aims to investigate transcriptomic changes and underlying pathological mechanisms in familial and sporadic idiopathic RLS to uncover potential contributors to its pathogenesis.Patients and Methods: This study included 37 RLS patients, 39 unrelated healthy controls and 19 healthy relatives of RLS patients with a positive family history. Messenger RNA (mRNA) extracted from the peripheral blood mononuclear cells of these participants was analyzed via next-generation sequencing, followed by GO and KEGG pathway analyses. Differentially expressed mRNAs were validated by RT-qPCR in a subset of patients and controls. The relationships between the expression levels and clinical indices were evaluated via correlation analysis.Results: After comparing with unrelated healthy controls and excluding genes with similar expression patterns in familial healthy controls, we identified nine upregulated and 28 downregulated mRNAs specifically in RLS patients. GO enrichment analysis indicated that these mRNAs are involved in protein binding and catalytic activity. KEGG analysis revealed that inflammation-related signaling pathways and cell adhesion molecules (CAMs) may be associated with RLS. Three specific mRNAs, including SPARCL1, CCL8 and SELE, demonstrated notably downregulated expression in RLS patients and were subsequently validated in a subset of 10 patients and 19 healthy controls.Conclusion: This study revealed differentially expressed SPARCL1, CCL8 and SELE in RLS patients, indicating the potential involvement of inflammatory pathways and CAMs in RLS pathogenesis. These findings further support the association between RLS, inflammation, and synaptic transmission, providing insights into potential diagnostic and therapeutic strategies targeting these pathways.Keywords: restless legs syndrome, peripheral blood mononuclear cells, bioinformatics, transcriptomics, inflammation, message-RNA sequencing